Genetic analysis of TPM1 gene polymorphism (rs11071720) in patients with non-syndromic cleft lip/palate in the south indian population : a case control study = Análisis genético del polimorfismo del gen TPM1 (rs11071720) en pacientes con labio/paladar hendido no sindrómico en la población del sur de la India : estudio de casos - Murugesan, Dhakshinya; Felicita, A. Sumathi; Priyadharshini Jayaseelan, Vijayashree (2025)
The aim of this study was to find out if there was an association between TPM1 gene polymorphism (rs11071720) and non-syndromic cleft lip and palate in humans. Twenty five patients with non-syndromic cleft lip and palate (NSCL/P) and twenty five healthy patients as controls were enrolled in the study. Whole blood drawn from the participants was used to obtain genomic DNA. Sequence specific primers were used to amplify the region spanning the polymorphic site of the TPM1 gene using polymerase chain reaction (PCR). The genotype of the subjects was identified employing the RFLP technique. The genotype and allele frequency distributions in the non-syndromic cleft lip and cleft palate patients and control groups were compared using Chi-square test. In the NSCL/P, the genotype in the order from highest to lowest frequency was TC (48%), followed by CC (32%) and TT (20%). Although the genotype frequency of the case and the control groups were found to be in agreement with Hardy Weinberg Equilibrium, the genotype frequencies TC, CC and TT of the polymorphism (rs11071720) among the two groups were not statistically significant which was evident from the p-value 0.8472. No significant association was found between TPM1 gene (rs11071720) polymorphism and NSCL/P.
El objetivo de este estudio fue descubrir si existía una asociación entre el polimorfismo del gen TPM1 (rs11071720) y el labio/paladar hendido no sindrómico en humanos. Se inscribieron en el estudio veinticinco pacientes con labio/paladar hendido no sindrómico (NSCL/P) y veinticinco pacientes sanos como controles. Se utilizó sangre entera extraída de los participantes para obtener ADN genómico. Se realizó la amplificación de la región que abarca el sitio polimórfico del gen TPM1 mediante la reacción en cadena de la polimerasa (PCR). El genotipo de los sujetos se identificó empleando la técnica RFLP. Las distribuciones de frecuencia de genotipos y alelos en pacientes con labio y paladar hendido no sindrómicos y en los grupos de control se compararon mediante la prueba de Chi-cuadrado. En el NSCL/P, el genotipo en orden de mayor a menor frecuencia fue TC (48%), seguido de CC (32%) y TT (20%). Aunque se encontró que la frecuencia genotípica del grupo de caso y de control concordaba con el equilibrio de Hardy Weinberg, las frecuencias genotípicas TC, CC y TT del polimorfismo (rs11071720) entre los dos grupos no fueron estadísticamente significativas, lo que era evidente a partir de la p-valor 0,8472. No se encontró ninguna asociación significativa entre el polimorfismo del gen TPM1 (rs11071720) y NSCL/P.
En revista Odóvtos, vol. 27, no.1 (enero-abril 2025)
Descripción basada en el contenido visto el 22 de abril, 2025
También disponible en formato HTML y EPUB